Інформаційна складова роботи відділу зв’язків з громадськістю в сучасних умовах - Байко, Оксана; Морушко, Олександр (Видавництво Львівської політехніки, 2014)
The question of the department of public relations in today's environment. The basic nature of this work.
Keywords: public relations; social communication; public information; egovernment; computerization of society